2023
DOI: 10.1021/acsenergylett.3c00969
|View full text |Cite
|
Sign up to set email alerts
|

Ester-Substituted Bispyridinylidenes: Double Concerted Two-Electron Bipolar Molecules for Symmetric Organic Redox Flow Batteries

Abstract: Organic redox-active molecules are promising materials for charge storage in redox-flow batteries (RFBs); however, the development of all-organic RFBs is hindered by material crossover, limited energy density, and poor stability of active materials. Here, ester-substituted bispyridinylidenes are reported as the first examples of intrinsic bipolar molecules that exhibit basically concerted double two-electron redox activity at a potential difference of 1.01 V. All three oxidation states of the pentylester deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Despite its conceptual simplicity, the role of ion pairs in the context of a two-electron redox process has been studied only in a few studies 26−30 and remains an underexplored territory in RFBs. 31,32 In this study, we delve into the utilization of ion pair formation to alter the redox behavior of naphthalene diimide (NDI) derivatives for nonaqueous organic RFBs. Our previous research revealed a remarkable redox stability of NDI, achieved in part by spin-pairing the singly reduced radicals into π−π stacked dimers in aqueous media.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its conceptual simplicity, the role of ion pairs in the context of a two-electron redox process has been studied only in a few studies 26−30 and remains an underexplored territory in RFBs. 31,32 In this study, we delve into the utilization of ion pair formation to alter the redox behavior of naphthalene diimide (NDI) derivatives for nonaqueous organic RFBs. Our previous research revealed a remarkable redox stability of NDI, achieved in part by spin-pairing the singly reduced radicals into π−π stacked dimers in aqueous media.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In aqueous environments, incorporating proton coupling has proven effective in reducing the barrier for redox reactions and, thus, accelerating the redox reaction rate. , For example, in acidic solutions, anthraquinone and benzoquinone derivatives were reported to exhibit a single two-electron transfer reaction, highlighting the importance of proton-coupled electron transfer (PCET) in aqueous RFBs. , This concept can be extended to other Lewis acid cations such as lithium (Li + ) or potassium (K + ), particularly in nonaqueous media where protons are not available. , While concerted electron/cation transfer is less likely compared to PCET due to the higher mass of the cations, their ionic nature and high effective charge should facilitate the dissipation of negative charge in the reduced redox species. Despite its conceptual simplicity, the role of ion pairs in the context of a two-electron redox process has been studied only in a few studies and remains an underexplored territory in RFBs. , …”
Section: Introductionmentioning
confidence: 99%
“…Along this path, open-shell compounds, acting as ambiphilic radicals with three stable states, have achieved significant success when appropriately managing their inherent reactivity [51,61,62,69] . The search for additional ambipolar compounds can be rooted in redox-active ligands featuring multiple stable states commonly found in homogeneous catalysis [63,64,70] or in organophotocatalysis characterized by three well-defined redox states [71] .…”
Section: Introductionmentioning
confidence: 99%
“…n corresponds to n-type molecules, p for p-type molecules, while Ab means for ambiphilic molecules. Examples of SORFBs based on strategy (A) could be found in the references [52][53][54][55][56][57][58] , strategy (B) at [49,50,59,60] and strategy (C) at [51,[61][62][63][64] .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the use of organic solvents offers an increased potential window, discovery of suitable electrolytes that allow access to extreme redox potentials (< −2 V for reduction and >+1 V for oxidation, , vs Fc/Fc + ) has been challenging due to the general scaling relationship of stability to energy density (i.e., the more extreme the potential, the more reactive the charged species). Therefore, developing electrolytes that balance stability and energy density to optimize the cell voltage remains a significant aim of the community.…”
Section: Introductionmentioning
confidence: 99%